A new snake of the genus Hydrops from Colombia A new snake of the genus Hydrops from Colombia - Dunn Emmett Reid (Caldasia)
While in Popayán recently Mr. F. C. Lehmann showed me the snakes in his care in the collection of the University of Cauca. Among them was a Hydrops which was taken in swampy terrain in the vicinity of the city (1760 m.) As Hydrops was supposed to be confined to the area east of the Andes this was quite a surprise. The species<span style="font-size: 12.0pt; font-family: ";Arial";,";sans-serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> seems to be undescribed and may be called: Hydrops lehmanni sp. nov. While in Popayán recently Mr. F. C. Lehmann showed me the snakes in his care in the collection of the University of Cauca. Among them was a Hydrops which was taken in swampy terrain in the vicinity of the city (1760 m.) As Hydrops was supposed to be confined to the area east of the Andes this was quite a surprise. The species<span style="font-size: 12.0pt; font-family: ";Arial";,";sans-serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> seems to be undescribed and may be called: Hydrops lehmanni sp. nov.